2012
DOI: 10.1186/1742-6405-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and population attributable risk among HIV/AIDS patients: comparison between NCEP-ATPIII, IDF and AHA/NHLBI definitions

Abstract: BackgroundMetabolic Syndrome (MetS) is based on the same individual components, but has received several amendments to the original definition. In this study, we verified the prevalence of metabolic syndrome according to different criteria, and the impact of each component on the diagnostic.MethodsThis cross-sectional study enrolled HIV infected patients from a HIV/AIDS reference Center in southern Brazil. Metabolic syndrome was identified according to the National Cholesterol Education Program Expert Panel on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
21
0
2
Order By: Relevance
“…Mercie et al observed significantly older age of patients diagnosed with LS and noticeably lower BMI and CD4+ T-lymphocyte count in comparison with cART-using patients with no LS [25]. In the majority of findings, LS features are found in patients treated with antiretroviral therapy [6,7].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Mercie et al observed significantly older age of patients diagnosed with LS and noticeably lower BMI and CD4+ T-lymphocyte count in comparison with cART-using patients with no LS [25]. In the majority of findings, LS features are found in patients treated with antiretroviral therapy [6,7].…”
Section: Discussionmentioning
confidence: 89%
“…In their research, patients on antiretroviral therapy were older and had significantly higher BMI. Lipodystrophy and lipohypertrophy were correlated to age and BMI, whereas lipoatrophy was only correlated to BMI, without any significant influence of age [6]. Mercie et al observed significantly older age of patients diagnosed with LS and noticeably lower BMI and CD4+ T-lymphocyte count in comparison with cART-using patients with no LS [25].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations